Utilizing Android Applications for Accounting Record-Keeping in MSMEs in the Era of Globalization - Andayani, Endro; Astuti, Wati Aris; Prasetiyani, Erni (STAI Miftahul ULa Nganjuk, 2024)
In the current era of globalization, access to information is becoming increasingly fast and easy, including in the field of accounting. MSMEs can now utilize Android devices for accounting record-keeping without the need for a computer. This community service aims to provide an understanding of Android-based accounting through online training via webinars, where participants can directly ask questions without the need to gather physically. An evaluation was conducted through a Q&A session at the end of the event. The results of the training showed that participants' paradigms were open, and their interest in registering businesses using smartphones increased. This training successfully raised their awareness about the importance of accounting record-keeping using mobile technology.